Isolation of a cDNA clone representing a gene with minimal expression in nit-4 mutant Neurospora crassa mycelia, yet not regulated by nitrate induction. - J. D. Colandene; R. H. Garrett (Fungal Genetics Reports, 1997)
We report the isolation of a cDNA clone containing a segment of DNA representing a gene which appears to require the nit-4 gene product for expression, yet is not regulated by nitrate induction. Such a cDNA is a novel finding with respect to the known function of the nit-4 gene.